A comprehensive review of hydrogen generation by water splitting using 2D nanomaterials: Photo vs electro-catalysis - Fares Almomani (12585685) (2023)
Transition metal carbides/nitrides (MXenes) with eccentric properties are emerging 2D nanomaterials with intriguing applications in the photo and electro-catalytic water splitting (Wsp). MXenes have a regular planer structure with a large specific surface area (SSA), excellent hydrophilicity, metallic conductivity, and a wide range of functionalities and surface termination groups, making them a promising candidate for long-term hydrogen generation (H2, gen). As a result, their use as electro and photo-catalysts in Wsp to solve energy and environmental challenges has increased. MXenes were proposed to overcome major drawbacks of TiO2, the most commonly used photo-catalyst in solar-driven Wsp, such as high band gap and fast recombination of photo-induced charge carriers. MXene has been rigorously investigated based on TiO2 modification (i.e. in-situ derived MXene-TiO2 and MXene/TiO2 nanocomposite) as well as Metal-MXene co-catalyst that provides simple electron channelization to improve overall electro and photo-catalytic activity (CatA)toward Wsp and increase the hydrogen evolution reaction (HER). However, several issues must be resolved before practical applications may be considered, such as weak environmental capabilities and limited intrinsic catalytic activities. Although there have been a few review papers on the synthesis, properties, and applications of Mxenes in various fields, this present work focuses on the most current advances in the synthetic of MXene-derived TiO2 and MXene/TiO2 nanohybrid composites as well as Metals-MXene nanocomposite, clarifying the charge carrier separation mechanism in connection to the formed Schottky junction at MXene- elements interface to attaining high photo-catalytic H2, gen. Furthermore, technical challenges, and enhanced catalytic performance as well as materials design and MXenes derivative with structural features and activity were presented. MXenes' catalytic mechanism is carefully outlined, along with its photocatalytic and electrocatalytic Wsp properties. According to the literature review, Ti3C2 can be combined with a variety of materials to produce electro or photo-catalysis with distinct layered morphology (0D, 1D, 2D, 3D), abundant surface termination groups, and enhanced photo-electrical activities. MXene-derived TiO2 and MXene/TiO2 nanohybrid composites have been proposed as viable electro and photo-catalytic H2, gen alternatives. The photo-catalytic H2, gen rate from Wsp over MXene-derived TiO2 can range from 20 to 50, 000 mol.g-1h−1, with Co-Chl@Ti3C2Tx producing the most. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2022.125905